Prevalence and allergy-related risk factors of overactive bladder in children in Northeast China - Zheng, Yue; Yin, Lu; Wang, Xiuli; Zhao, Chengguang; Du, Yue (Frontiers in Public Health, 2024)
Objective The objective of this study was to investigate the prevalence of overactive bladder (OAB) and its risk factors related to allergies among children in Northeastern China. Methods A community survey on OAB was conducted in Northeast China from 1 April 2022 to 30 April 2022. The survey targeted children aged 5–14 years and utilized questionnaires. A total of 1,394 children were enrolled, and their parents were requested to fill out a questionnaire to provide basic information about the children. This encompassed details regarding the presence or absence of urgent urination unrelated to urinary tract infection, urinary tract infection, allergic rhinitis, asthma or cough variant asthma, atopic dermatitis, anaphylactic conjunctivitis, urticaria, constipation, and attention deficit hyperactivity disorder (ADHD). The prevalence of OAB was calculated. The chi-squared test was used to analyze OAB-related factors, which were subsequently included in the logistic regression model for multi-factor analysis. Results The overall OAB prevalence was 10.7% (120 of 1,121), including 47 mild cases (39.2%), 71 moderate cases (59.1%), and 2 severe cases (1.7%). OAB prevalence decreased with age (p < 0.05). The risk factors associated with OAB were allergic asthma (OR = 1.87, 95%CI: 1.12–3.13), atopic dermatitis (OR = 2.45, 95%CI: 1.61–3.73), anaphylactic conjunctivitis (OR = 1.61, 95%CI: 1.07–2.42), and urticaria (OR = 1.93, 95%CI: 1.40–2.66). Conclusion OAB prevalence among children in Northeastern China was found to be 10.7%, with its risk factors being allergic asthma, anaphylactic conjunctivitis, urticaria, and atopic dermatitis. The identification of allergy-related risk factors may provide new ideas for the prevention and treatment of OAB.